Inhibition of prostaglandin E2 receptor EP3 mitigates thrombin-induced brain injury. Issue 6 (June 2016) - Han, Xiaoning; Lan, Xi; Li, Qiang; Gao, Yufeng; Zhu, Wei; Cheng, Tian; Maruyama, Takayuki; Wang, Jian
Prostaglandin E2 EP3 receptor is the only prostaglandin E2 receptor that couples to multiple G-proteins, but its role in thrombin-induced brain injury is unclear. In the present study, we exposed mouse hippocampal slice cultures to thrombin in vitro and injected mice with intrastriatal thrombin in vivo to investigate the role of EP3 receptor in thrombin-induced brain injury and explore its underlying cellular and molecular mechanisms. In vitro, EP3 receptor inhibition reduced thrombin-induced hippocampal CA1 cell death. In vivo, EP3 receptor was expressed in astrocytes and microglia in the perilesional region. EP3 receptor inhibition reduced lesion volume, neurologic deficit, cell death, matrix metalloproteinase-9 activity, neutrophil infiltration, and the number of CD68 + microglia, but increased the number of Ym-1 + M2 microglia. RhoA-Rho kinase levels were increased after thrombin injection and were decreased by EP3 receptor inhibition. In mice that received an intrastriatal injection of autologous arterial blood, inhibition of thrombin activity with hirudin decreased RhoA expression compared with that in vehicle-treated mice. However, EP3 receptor activation reversed this effect of hirudin. These findings show that prostaglandin E2 EP3 receptor contributes to thrombin-induced brain damage via Rho-Rho kinase–mediated cytotoxicity and proinflammatory responses.